Online school and the risk of myopia booming in school age children during the COVID-19 pandemic - Baswedan, Rizki Hafidzah (BKM Public Health and Community Medicine, 2021)
Purpose: To describe shifts in gadgets usage for online schools during the Covid-19 pandemic and the potential for visual impairment in children based on a literature review. Contents: The Covid-19 pandemic has impacted all aspects of life, including the change in learning methods from offline to online. These led to a lack of outdoor activities and increased gadgets usage, especially among school children. Gadgets usage in children could cause visual disturbances in the form of myopia, so it needs to be limited. A cohort study in Rotterdam found an association between computer use and the incidence of myopia in 9-year-olds. A study in Hong Kong compared the duration of smartphone use before and during the Covid-19 pandemic with the incidence of myopia in school-age children. These studies showed an increase in myopia prevalence three times after the pandemic. These can become a public health problem in the future if not prevented early. We recommend that children spend at least 2 hours in an open area to help improve their eyesight. Parents also need to be more aware of eye complaints in their children. Routine annual eye examinations also need to be carried out to detect early vision problems to prevent myopia progression.